K KAJIAN KARAKTERISTIK BATUAN BEKU ANDESIT SEBAGAI BAHAN BANGUNAN DI DAERAH SULAMADAHA KECAMATAN TERNATE BARAT KOTA TERNATE - Karim, Razak -; Suriadi, Sahdan (Fakultas Teknik UMMU, 2019)
The potential of andesite igneous rock caused by volcanic activity, makes the City of Ternate has the potential of rock and sand extraction which is very abundant. Therefore this research was conducted to determine the characteristics of andesite rocks based on the results of testing physical and mechanical properties in the Laboratory, and how to determine the feasibility and non-feasibility of the availability of these andesite rocks as building construction raw materials in accordance with Standards. The study was carried out in the Sulamadaha area of ??Ternate City, where testing of rock samples was carried out at the SABO Laboratory, Center of Water Resources Research and Development in Yogyakarta and testing of other rock aggregate samples was carried out in the Laboratory of Structur and Materials in Civil Engineering Department, Khairun University in Ternate. Description of rocks has a fine solid gray color, afanitic textured crystalline subhedral, with mineral compositions contained in them are orthoclase feldspard, plagioclase, and quartz. The average compressive strength of andesite rocks from four samples is 1.357,015 kg/cm², for the test results the maximum shear resistance is 29,85%, while the average test results of water absorption ability in andesite rocks are 3,67 %. So it was concluded that andesite igneous rocks of Sulamadaha area, West Ternate District were feasible and fulfilled the requirements and quality of natural stone for building materials in accordance with Indonesian Industrial Standards (SII-0378-80).